Determination of Specificity and Biochemical Characteristics of Neutral Protease Isolated from Myceliophthora thermophila - Hamin Neto, Youssef A. A.; Oliveira, Lilian C. G. de; Oliveira, Arthur H. C. de; Rosa, Jose C.; Juliano, Maria A.; Juliano, Luiz; Rodrigues, Andre [UNESP]; Cabral, Hamilton (Bentham Science Publ Ltd, 2015)
Proteases hydrolyze polypeptides to release peptides and/or amino acids. This subclass of enzymes is among those with the most sales worldwide, particularly those produced by microorganisms. Proteases may be applied in the several industries, including the food industry, leather, detergents, and bioremediation. Myceliophthora thermophila protease was produced by a submerged bioprocess and then purified 185-fold by anion exchange and hydrophobic chromatography with a 37% yield. The molecular mass was estimated at 36.2 kDa, and mass spectrometry identified two sequences: GVVANMSLGGSYSASINNAAAALVR and STGNAAITGVPSGTTNR. The isolated protein was characterized biochemically, showed an optimum pH of 6.5 and optimum temperature of 45 degrees C, and stability at wide range of pH and temperatures and in the presence of reducing agents and some surfactants. Kinetic assays for this enzyme showed a greater catalytic efficiency when the substrate had alanine at position P-2'. The protease presented characteristics that may be of interest to many industrial areas.
Keywords: FRET substrates; neutral protease; mass spectrometry; Myceliophthora thermophila; purification; stability